Bone health in a cohort of irish duchenne muscular dystrophy patients. (4th April 2011) - McSweeney, N; McDonnell, C; Murphy, N; McKenna, M; Webb, D; Vanderkampf, S; Kilbane, M; Lynch, B
Abstract : Introduction: Reduced mobility in Duchenne Muscular Dystrophy (DMD) leads to the development of osteopenia and osteoporosis leading to increased bone fragility and risk of fracture. Dietary Vitamin D and calcium intake is suboptimal in most children. Reduced Vitamin D levels have been reported recently in children with DMD. Objectives: (1) To determine the incidence of osteopenia and fractures in an Irish cohort of children with DMD and correlation with quality of life and (2) Incidence of Vitamin D deficiencies, seasonal variation and response to supplementation. Methods: Retrospective case note review. Prospective measurement of markers of bone turnover at two time intervals, pre and post supplementation with Vitamin D and calcium. Measurement of bone mineral density using DXA. Dietary assessment of Vitamin D. Administration of Peds QL questionnaire to ascertain quality of life. Results: 45 patients (age range 5 years 4 months–18 years 9 months, mean age 9 years 7 months, 25 ambulant) had DXA performed. Mean lumbar spine Z score in the whole group was −1.6 and −0.8 at total body. Mean estimated calcium intake was 1246 mg/d in the whole group, 1205 mg/d in ambulant group, and 781 mg/d in the nonambulant group. Of the 25 ambulant patients (median 7 years 9 months), 17 were on steroids (median duration 19 months). Mean Z score at the lumbar spine was −1.28(range 0.1 to −4.3), mean Z score at total body was −0.3 (4.7 to −2.9). In the nonambulant group (n=20, median 4 years since loss of ambulation) mean Lumbar Spine Z score was −2.5 (range −0.7 to −4.1) and mean total body Z score (16/20) was −1.6(range+8.2 to −4.1). Mean baseline Vitamin D levels measured in Winter in 32/45 was 38.5 (18.7−63.5). Repeat mean Vitamin D levels measured after 6 months supplementation was 52.9 (17.7−66.5). 11 of 45 had sustained fractures, 5 when still ambulant. Six had delayed bone age and osteopenia on x-ray. Conclusion: Vitamin D levels are suboptimal in most boys with DMD and remained so despite supplementation. Bone density was also reduced in the majority but more so in the nonambulant group. There was no correlation between reported quality of life and level of osteopenia.